Efek Penambahan Pati Talas Belitung Terhadap Karakteristik Fisik dan Sensoris Nugget Ayam dengan Substitusi Jamur Tiram - Hikmah Yuliasari; Kavadya Syska; Laksmi Putri Ayuningtyas (Scientific Timeline, 2021)
This work aimed to evaluate the effect of taro (Xanthosoma sagittifolium) starch addition as filler on the physical and sensory properties of oyster mushroom substituted chicken nugget. This research used a complete randomized design with two factors: 1) chicken and oyster mushroom proportion and 2) taro starch percentage. Additional taro starch percentages of 10% (K1), 20% (K2), and 30% (K3) significantly affect the hardness of chicken nuggets. On the other hand, the increasing proportion of oyster mushroom to chicken affect vice versa. The chicken and oyster mushroom proportion of 25:75 (F4) on the additional percentage of 20% (K2) and 30% (K3) showed a higher mean value than 10%taro starch addition (K1). The highest hedonic score was chicken nugget with 75% (F4) and 100% (F5) oyster mushroom addition, ranged from 3.80 (quite like) and 4.20 (like). In contrast, taro starch addition as filler had no significant effect on the nugget's hedonic score.